The riddle of the greywacke: a story of friendship and rivalry, failure and success. (17th May 2021) - Davidson, Nick
Abstract : In the early 1800s, two of the greatest geologists of the nineteenth century set out to solve one of the big riddles of the age: the early history of the Earth. This is the story of the moment when one of the greatest scientific collaborations of Victorian Britain turned into a bitter and destructive rivalry that dominated the new science of geology for two decades.